Evaluation of anxiolytic properties of BacoMind extract of plant Bacopa monnieri Linn. in comparison with diazepam in rodent model - Rathore, Rajni; Arora, Tarun; Mamadi, Rashmi Karabasappa (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Anxiety is a state characterized by somatic, emotional, cognitive, and behavioral components, associated with significant disability. The pharmacotherapy for anxiety remains limited for achievable safety and tolerability of the medicines. Benzodiazepines use associated with side effects like psychomotor impairment and addiction liability. Due to the ADRs associated with antianxiety drugs, the drug trials have focused on screening herbal medicines that are reportedly used in the treatment of anxiety and which have minimal side effects. Methods: The anxiolytic activity was examined by using the elevated plus maze (EPM) and open field test (OFT), forty Albino wistar strain rats of both sex of weighing 120 to 200 g were divided into four groups of ten rats each.. Group 1 received vehicle (normal saline); group 2 received diazepam (1 mg/kg); groups 3 and 4 received BacoMind™, 30 and 60 mg/kg oral, respectively. Results: Rats treated with diazepam (1 mg/kg, p.o.) showed significant (p<0.001) increase in the percentage of open arms entries and time spent whereas, in closed arm the number of entries and time spent were significantly (p<0.05) decreased. Intraperitonial administration of BacoMind™ extract of plant Bacopa monnieri Linn. exhibited significant (p<0.05) increase in the number of open arm entries and time spent with significant (p<0.05) reduction in number of entries and time spent in the closed arm as compared to group 1. BacoMind™ treated rats also produced significant increase in the number of rearings (p<0.05), assisted rearings and number of squares crossed (p<0.01). Conclusions: BacoMind™ extract of plant Bacopa monnieri Linn possess significant anxiolytic activity in the rats. It can be a promising anxiolytic agent.